The Relationship between Stress and Incidence of Sleep Disorder among Students at the Faculty of Medicine Universitas Sumatera Utara - Ibnati Amira Hamdi Hamdi; Nuraiza Meutia; Sabri Ibrahim; Tasrif Hamdi (Sumatera Medical Journal, 2022)
Abstract. Stress is a non-specific response of the body to any form of changes. Stress is generally considered synonymous with distress. Long study duration and high academic achievement targets have the potential to cause stress in medical students. Prolonged stress can cause sleep disturbances in a person. Sleep disorders are a group of conditions that can disrupt sleep patterns. Objective. The purpose of this study was to determine the effect of stress on sleep disorders in undergraduate students at the Faculty of Medicine, Universitas Sumatera Utara. Methods. This research is an analytic study with a cross-sectional design. Respondents are undergraduate students at the Faculty of Medicine, University of North Sumatra, class of 2018-2021. Data was obtained through a questionnaire instrument. Results. Of the 103 respondents, 58 (56.3%) reported experiencing stressful events with sleep disturbances. Conclusion. There was a significant relationship (P = 0.047) between stress and sleep disorders in students at the Faculty of Medicine, University of North Sumatra. In majority, the type of their sleep disorder are nightmares.